URGENSI MAJELIS TAKLIM SEBAGAI LEMBAGA DAKWAH DI MASYARAKAT - Mujahidin Mujahidin (Alhadharah: Jurnal Ilmu Dakwah, 2018)
The existence of majlis taklim in society becomes very important. This is because the assembly taklim has a position and a strategic role, in conveying the values of da'wah in the community more specifically to the mothers of the religious sciences. In addition, the assembly became a means of communication and means to strengthen the fraternity among fellow Muslims. In addition, the assembly taklim can serve as a medium in the mental mental development of Islamic societies in the face of the current era of information globalization. Therefore it can be used as a medium of enlightenment and community empowerment. In other words, the existence of majelis taklim generally can be utilized by all circles of society as non-formal education institutions.